2017
DOI: 10.17269/cjph.108.5728
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis for the adverse effects, immunogenicity and efficacy of Lyme disease vaccines: Guiding novel vaccine development

Abstract: BACKGROUND: Lyme borreliosis (LB) is the most prevalent arthropod-borne infectious disease in North America. Currently, no vaccine is available to prevent LB in humans, although monovalent and multivalent vaccines have been developed in the past.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Furthermore, others found that vaccine-induced immune responses to rOspA did not replicate the sequence of events needed in natural infection to induce treatment-resistant Lyme arthritis 45 . More recent systematic reviews and meta-analysis of published data have found that reported adverse events were not different between vaccinated and placebo groups 46 , 47 .…”
Section: Clinical Trials Of the Recombinant Ospa (Rospa) Vaccine For Lyme Disease Preventionmentioning
confidence: 96%
“…Furthermore, others found that vaccine-induced immune responses to rOspA did not replicate the sequence of events needed in natural infection to induce treatment-resistant Lyme arthritis 45 . More recent systematic reviews and meta-analysis of published data have found that reported adverse events were not different between vaccinated and placebo groups 46 , 47 .…”
Section: Clinical Trials Of the Recombinant Ospa (Rospa) Vaccine For Lyme Disease Preventionmentioning
confidence: 96%
“…No further work on this topic is warranted as a systematic review was recently published (60). Lyme vaccines are currently approved and used in dogs, and there has not been a commercial vaccine available for humans since the withdrawal of LYMErix in 2002 (61)(62)(63)(64).…”
Section: Scoping Reviewmentioning
confidence: 99%
“… Zhao et al (2017) concluded that whilst side-effects were rare, further research on efficacy and safety was needed. Badawi et al (2017) compared monovalent vaccines (LYMErix, ImmuLyme) (neither currently available) with preliminary data for next-generation multivalent vaccines and concluded that the multivalent vaccine was slightly more tolerable than the monovalent one, which in turn was not worse than other vaccines in the USA-based Vaccine Adverse Event Reporting System (VAERS). Despite approval for the LYMErix vaccine by the US Food and Drug Administration (FDA), the LYMErix vaccine was voluntarily withdrawn from the market, in 2002, due to poor sales.…”
Section: Introductionmentioning
confidence: 99%
“…Despite approval for the LYMErix vaccine by the US Food and Drug Administration (FDA), the LYMErix vaccine was voluntarily withdrawn from the market, in 2002, due to poor sales. The replacement of monovalent vaccines with vaccines that have a similar approach may, therefore, not be the best method for new vaccine development ( Badawi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%